Diffuse Increased Sodium Fluoride Gastric Activity in a Patient With Hypercalcemia. (September 2017) - Shao, Fuqiang; Zhang, Shumao; Qi, Chi; Wang, Yu; Chen, Yue
Abstract : Abstract: Increased extraosseous uptake of sodium fluoride can be visualized because of many different etiologies. A 62-year-old man with a history of osteoporosis had an 18 F–sodium fluoride PET/CT scan for accessing chest pain caused by an accident. The images showed multiple fractures. Unexpectedly, diffuse activity was noted in the gastric wall, which was suggestive of possible hypercalcemia. The serum calcium level confirmed the patient had hypercalcemia.